ANALYSIS OF EFFECT OF PROFITABILITY, ASSETS STRUCTURE, SIZE OF COMPANIES, AND LIQUIDITY TO CAPITAL STRUCTURES IN MINING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2012 - 2015 - Ahmad, Gatot Nazir; Lestari, Ripa; Dalimunthe, Sholatia (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
The purpose of this study is to analyze the effect of profitability, structure assets, firm size and liquidity to the capital structure of mining companies listed on the Indonesia Stock Exchange for the period 2012-2015. Sampling technique using purposive sampling. Data analysis technique used in this research is panel data regression. The results showed that partially profitability had negative and significant effect to capital structure, asset structure had positive and significant effect to capital structure, firm size had positive and significant effect to capital structure, and liquidity had negative and significant effect to capital structure. Simultaneously profitability, asset structure, firm size and liquidity have a significant effect on capital structure.